Do government guarantees really matter in fixed exchange rate regimes? - Marcio Magalh\~aes Janot; Márcio Gomes Pinto Garcia (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2018)
Since the mid 1990s, theories of speculative attacks have argued that fixed exchange rate regimes induce excessive borrowing in foreign currency as an optimal response to implicit guarantees that the government will not devalue the domestic currency. Using data on Brazilian firms before and after the end of the fixed exchange rate regime in 1999, we estimate the relevance of the government guarantees by comparing the changes in foreign debt of two groups of firms: those that hedged their foreign currency debt prior to the exchange rate float and those that did not. Using the difference-in-differences approach, in which firm-specific characteristics are introduced as control variables, we exclude the macroeconomic effects of the change in the exchange rate regime and the possible differences in foreign debt trends of the two groups of firms, thus obtaining an estimate of the impact of the government guarantees on borrowing in foreign currency. The results suggest that the guarantees do not induce excessive borrowing in foreign currency
Keywords: F31; F34; G15; G18; 330; Foreign Exchange Risk; Government Guarantees; Exchange rate regime; Hedging